2006
DOI: 10.1369/jhc.4a6603.2006
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Telomerase Reverse Transcriptase Subunit (TERT) and Telomere Sizing in Pig Ovarian Follicles

Abstract: (DF) S U M M A R Y Telomerase is crucial for chromosome stability because it maintains telomere length. Little is known about telomerase in ovarian follicles, where an intense cell division is crucial to sustain estrous cycle and to drive oocyte development. The present research was performed to detect, by immunohistochemistry, the distribution of telomerase catalytic subunit (TERT) during folliculogenesis and to study the effect of TERT expression on telomeres. To this aim, telomere length has been measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 51 publications
(69 reference statements)
2
47
0
Order By: Relevance
“…Our recent studies showing that estrogen deficiency caused telomerase inhibition in the adrenal gland (Bayne et al, 2008) suggest that estrogen links the regulation of telomere homeostasis in steroidogenic organs in mice. The regulation of ovarian telomerase, present in a number of species including mice, rats, cows, pigs and humans (Lavranos et al, 1999;Rodgers et al, 2001;Yamagata et al, 2002;Baykal et al, 2004;Russo et al, 2006), is likely to be physiological, underlying major functions of the ovary. Our findings that estrogen increases telomere length in 3-4-week-old ArKO mice suggest that estrogen deficiencyassociated telomerase inhibition is due to the lack of estrogen stimulation of telomerase, since the inhibition is reversed by estrogen replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies showing that estrogen deficiency caused telomerase inhibition in the adrenal gland (Bayne et al, 2008) suggest that estrogen links the regulation of telomere homeostasis in steroidogenic organs in mice. The regulation of ovarian telomerase, present in a number of species including mice, rats, cows, pigs and humans (Lavranos et al, 1999;Rodgers et al, 2001;Yamagata et al, 2002;Baykal et al, 2004;Russo et al, 2006), is likely to be physiological, underlying major functions of the ovary. Our findings that estrogen increases telomere length in 3-4-week-old ArKO mice suggest that estrogen deficiencyassociated telomerase inhibition is due to the lack of estrogen stimulation of telomerase, since the inhibition is reversed by estrogen replacement therapy.…”
Section: Discussionmentioning
confidence: 99%
“…To determine telomere size, using the fluorescence in situ hybridization (FISH) technique, the oocytes were processed within their follicle structures, according to Russo et al (2006), dehydrated through ethanol series, and then embedded in paraffin wax.…”
Section: Materials and Methods Tissue And Oocyte Collectionmentioning
confidence: 99%
“…The TERT component of telomerase is the primary determinant for enzyme activity and its expression is correlated to cells with telomere elongation (Cong et al, 1999;Misiti et al, 2000;Wang et al, 2000). Recently, TERT component has been related to the process of telomere rearrangement in pig germ cells during oogenesis where the presence of the enzyme within the nucleus has been strictly correlated to progressive telomere elongation (Russo et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Analysis (by immunohistochemistry and fluorescence in situ hybridization) of the distribution of TERT during folliculogenesis and its correlation with telomeres in porcine ovarian primary and preantral follicles showed that TERT is expressed in granulosa cells with a typical nuclear location, and that its expression correlates with the size of telomeres. Long telomeres were seen from preantral to antral follicles (Russo et al 2006). Telomerase activity was detected in two distinct populations of porcine granulosa cells: relatively undifferentiated granulosa cells isolated from small (1-2 mm) antral follicles and differentiated cells with advanced functionality obtained from large (5-7 mm) antral follicles (Tomanek et al 2008).…”
Section: Role Of Telomerase In Granulosa Cell Proliferation During Fomentioning
confidence: 99%